Quality of water and milk in manual milking systems in the Northern Sierra of Ecuador - Contero, Rocío (2021)
The aim of this study was to determine the quality of the water used during manual milking and its influence on the microbiological quality of the milk. In total 63 cattle producers from communities located in Cayambe and Pedro Moncayo in the Sierra Norte region of Ecuador were included in the study. The samples were collected in the productive units where they perform the milking, in which 98% did not have drinking water. The population was categorized into two groups: those that use drinking water, transported in containers (G1) and those that use water collected from other sources (rain or irrigation) (G2) for the milking process. G1 presented water and milk of acceptable quality: total coliforms <50 MPN/100 ml; absence of faecal coliforms and CBT <200x103 CFU/ml, while the water and milk samples from G2 showed total coliforms exceeding the permissible limits, presence of faecal coliforms (29%) and CBT >900x103 CFU/ml. In both groups, the surface analysis of aerobic mesophiles in the collection jars showed inappropriate cleaning (>400 CFU/cm2). These findings indicated that the quality of the water used is one factor that affect the microbiological quality of the milk.